KARYOLOGICAL SCREENING OF ANESTROUS HEIFERS - Baghela, Sunita; Joshi, Shrikant; Ignitious, Sherly (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Fertility is a multifactorial phenomenon which is influenced by several factors that often overlap. Unlike many other causes of reproductive failure, little attention appears to be given towards cytogenetic anomalies in farm animals (Yimer and Rosnina, 2014). Chromosomal abnormalities, such as translocations, tandem fusion and chimerism for sex cells, sex chromosome aneuploidy are among few important abnormalities in cattle, which are reported to be associated with variable degrees of infertility. Present study was undertaken to find out the incidence of chromosomal defects in reproductively abnormal animals and to recommend suitable strategies to eradicate such chromosomal abnormalities from the population